Molecular biology of Alzheimer's disease : genes and mechanisms involved in amyloid generation - Haass, Christian (Harwood Academic Publishers, 1998)
Highlighting the latest and the most timely aspects of Alzheimer's disease research, this text will enable scientists in related research fields, as well as physicians working with Alzheimer's disease patients, to obtain a quick and complete overview of the current state of the art in one of the most exciting fields in neuroscience research. Leading scientists have contributed articles focusing on key developments in this field. This includes an overview about the pathology, the genetics of familial Alzheimer's disease, proteolytic generation and aggregation of amyloid -peptide, presenilins, r.